Kimura's Disease with Bilateral Auricular Masses - Hiwatashi, Akio (AJNR Am J Neuroradiol, 1999)
Summary: We report an unusual case of Kimura's disease. An 81-year-old Japanese woman was shown to have bilateral auricular masses that had begun to enlarge 6 years before. On CT scans, slightly high-density masses with faint contrast enhancement were seen. The masses were heterogeneous and hypointense on T1-weighted MR images, were slightly hyperintense on T2-weighted MR images, and showed heterogeneous enhancement after the administration of contrast material. Kimura's disease should be included in the differential diagnosis of bilateral auricular tumors.